PENGARUH STRATEGI PEMBELAJARAN JOYFUL LEARNING BERBANTUAN PERMAINAN ROCQ TERHADAP MINAT DAN HASIL BELAJAR SISWA - Putri, Dwi Ditha; Enawaty, Eny; Sahputra, Rachmat (Universitas Tanjungpura, Prodi Pendidikan Kimia, 2023)
The purpose of this research is to determine the difference of student learning interest and students learning outcomes with the influence of joyful learning strategies with ROCQ (Ranking One Chemistry Quiz) game on the results of student learning outcomes. This study employed a Quasi-Experimental Design with